2020
DOI: 10.3389/fpsyt.2020.00272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ZiBuPiYin Recipe on Diabetes-Associated Cognitive Decline in Zucker Diabetic Fatty Rats After Chronic Psychological Stress

Abstract: Background: Cognitive impairment is a complication of type 2 diabetes mellitus (T2DM) that affects the central nervous system (CNS). Studies have shown that chronic psychological stress may promote the development of T2DM into diabetes-associated cognitive decline (DACD). Previously, cognitive impairment in T2DM was correlated predominantly with insulin resistance in the medial prefrontal cortex (mPFC). Aims:We examined the effect of the ZiBuPiYin recipe (ZBPYR) on Zucker diabetic fatty (ZDF) rats and explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…ZiBuPiYin recipe (ZBPYR) is derived from a modification of ZiCheng decoction, a TCM recipe recorded in a TCM monograph named Bujuji written by Wu Cheng during Qing dynasty. Our preliminary study suggested that ZBPYR improved learning and memory ability in multiple animal models of diabetes [ 10 12 ]. We also found that ZBPYR protected hippocampal neurons against glutamate and amyloid beta-peptide- (A β -) induced neurotoxicity through blocking the serum-inducible kinase and spine-associated Rap GTPase-activating protein (SNK-SPAR) pathway [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…ZiBuPiYin recipe (ZBPYR) is derived from a modification of ZiCheng decoction, a TCM recipe recorded in a TCM monograph named Bujuji written by Wu Cheng during Qing dynasty. Our preliminary study suggested that ZBPYR improved learning and memory ability in multiple animal models of diabetes [ 10 12 ]. We also found that ZBPYR protected hippocampal neurons against glutamate and amyloid beta-peptide- (A β -) induced neurotoxicity through blocking the serum-inducible kinase and spine-associated Rap GTPase-activating protein (SNK-SPAR) pathway [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brain Aβ deposition is a hallmark of DACD and AD pathogenesis, as well as an important cause of cognitive decline (Sui et al, 2017). Recent studies have also confirmed the similarities between the changes seen in ZDF rats and brain samples from people with AD, namely, Aβ accumulation and insulin resistance in the brain causing neuronal injury and ultimately cognitive decline (Bi et al, 2020;Jash et al, 2020). The insulindependent IRS2-AKT signaling pathway is the main pathway of insulin resistance (Zhang L. et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…The spatial memory ability of 15-week-old rats was performed by the MWM test as described in our previous study (Bi et al, 2020). All rats were trained in a round water pool at 22 ± 2 • C with four equal quadrants.…”
Section: Morris Water Maze (Mwm)mentioning
confidence: 99%
See 2 more Smart Citations